Prevent with Pleasure: A systematic review of HIV public communication campaigns incorporating a pleasure-based approach. - Luke Muschialli; Jessie V Ford; Lianne Gonsalves; Robert Pralat (PLOS Global Public Health, 2025)
Previous research suggests integrating pleasure into HIV prevention programming improves health outcomes. There are no existing reviews on how exactly pleasure is used within HIV public communications campaigns (PCCs). This manuscript investigates: (1) how HIV PCCs operationalise pleasure; and (2) the efficacy of pleasure-based HIV PCCs. EMBASE, Web of Science Core Collection and PsycINFO were searched for articles that present pleasure-based HIV PCCs on 13/12/2023 (PROSPERO ID: CRD42023487275) with no language restrictions. A narrative synthesis on pleasure operationalisation centred around three inductively coded categories: Enjoyment, Emotional Connection and Empowerment. Another narrative synthesis summarised efficacy data around six categories of HIV-related outcomes. 19,238 articles were retrieved, with 47 articles included in analysis, describing 29 campaigns. 65.5% of interventions operationalised Empowerment, 48.3% Enjoyment, and 31.0% Emotional Connection, with narrative synthesis highlighting the diverse ways this was achieved across target communities. An analysis of efficacy identified heterogeneous outcome reporting with inconsistent results across studies, but important outcomes, such as stigma reduction and condom use, were positively associated with intervention exposure across all relevant interventions. We highlight a range of mechanisms through which pleasure can be operationalised, which should inform future intervention development, even if the extant literature weakly supports the efficacy of such interventions.